2017
DOI: 10.1038/s41598-017-16564-2
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic value of thyroid hormones in acute ischemic stroke – a meta analysis

Abstract: Previous studies on the association between thyroid hormones and prognosis of acute ischemic stroke (AIS) reported conflicting results. We conducted a meta-analysis to assess the prognostic value of thyroid hormones in AIS. The PubMed, EMBASE, and Cochrane library databases were searched through May 12, 2017 to identify eligible studies on this subject. Out of 2,181 studies retrieved, 11 studies were finally included with a total number of 3,936 acute stroke patients for analysis. Odds ratio (OR) for predictin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 58 publications
1
28
0
1
Order By: Relevance
“…We also found that FT3 levels were negatively correlated with IS incidence among young adults. This is the rst study to our knowledge to have reported such a relationship, as prior studies and meta-analysis have largely focused on correlations between low FT3 levels and severity/mortality among acute IS patients [23][24][25][26][27]. These prior studies have reported such a relationship even for low FT3 values within the standard reference range [28,29].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We also found that FT3 levels were negatively correlated with IS incidence among young adults. This is the rst study to our knowledge to have reported such a relationship, as prior studies and meta-analysis have largely focused on correlations between low FT3 levels and severity/mortality among acute IS patients [23][24][25][26][27]. These prior studies have reported such a relationship even for low FT3 values within the standard reference range [28,29].…”
Section: Discussionmentioning
confidence: 74%
“…One study, however, found that this relationship was age-dependent, such that TT3 and FT3 levels were unrelated to IS outcomes in patients < 65 years old, whereas TT3 levels were independently predictive of poor outcomes among older patients [30]. In these prior studies, the average population ages ranged from 61.4-81.5 years [23][24][25][26][27][28], with the exception of one study with a median population age of 48 years [29]. Serum TT3 and FT3 levels are lower among healthy older individuals [31], and FT3 levels decline over time [32].…”
Section: Discussionmentioning
confidence: 99%
“…For example, an inverse relation between free T 3 levels and the risk for developing Alzheimer's disease (AD) was demonstrated in a 302 patient cohort with mild cognitive impairment at the beginning of the study (Quinlan et al, 2019). Similarly, lower free T 3 levels in pre-stroke individuals correlated with increased stroke severity, disability and mortality rates (Jiang et al, 2017;Lamba et al, 2018).…”
Section: Patient Studies Linking Thyroid Hormone Levels With Cns Injumentioning
confidence: 99%
“…Their median age was 69 (62-75) years, with men being the predominate gender (58.8 %). The median NIHSS score was 7 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Among all the patients, 80 (31.4 %) patients received specific intravenous thrombolysis treatment.…”
Section: Baseline Characteristics Of Study Populationmentioning
confidence: 99%
“…Among these hormones, T3 has the highest prognostic value in AIS. Low serum levels of T3, even within normal ranges, are associated with worse functional prognosis after ischaemic stroke, but are equivocal for mortality [7]. Low T3 concentration with normal or slightly reduced TSH is seen in many disorders [8].…”
Section: Introductionmentioning
confidence: 99%